Existential and Nostalgic Perspectives of William Faulkner’s The Sound and the Fury - Sao, Surendra Kumar (International Journal of Language and Literary Studies, 2024)
William Faulkner, a renowned Southern author, is known for his portrayal of the decline of the privileged social class and the Southern United States after the Civil War. His narratives often depict decaying homes and the lives of distinguished individuals who maintain antiquated Southern beliefs. The Sound and the Fury by William Faulkner is a profound and intricate novel that explores the intricacies of human existence. The novel follows the Compson family, who reside in Jefferson, Mississippi, and Cambridge, Massachusetts, through pivotal events such as Caddy’s ascent, Benjy’s alteration of name, Caddy’s gestation and nuptials, Quentin’s demise, Benjy’s emasculation, and Mr. Compson’s deterioration due to immoderate alcohol consumption. Faulkner employs innovative storytelling techniques such as stream of consciousness and a nonlinear plot structure, adding complexity to the work while also offering deep satisfaction to readers. The novel is notable for the profound complexity of its characters, each possessing intricate and diverse qualities that enhance the depth and complexity of the storyline.